Acute Pancreatitis Caused by Isolated Pancreatic Metastasis From Uterine Choriocarcinoma. (September 2019) - Muktesh, Gaurav; Mitra, Suvradeep; Sinha, Saroj K.; Dhaka, Narendra; Saikia, Uma N.; Sarma, Phulen; Gulati, Ajay; Samanta, Jayanta; Kochhar, Rakesh
Abstract : Choriocarcinoma is an aggressive gestational trophoblastic neoplasia known for its widely metastatic potential. However, isolated pancreatic metastasis is an extremely rare occurrence and has not been documented in the English literature to the best of our knowledge. The metastatic deposits in the index case led to widespread hemorrhage and necrosis of the pancreatic parenchyma, causing severe acute pancreatitis. The patient succumbed to her illness before chemotherapy was administered. Thus, we present an autopsy case of a uterine choriocarcinoma with isolated pancreatic metastasis presenting as severe acute pancreatitis in a 27-yr-old woman following a molar pregnancy.